Seed morphology of some taxa of the genus Euphorbia L. (Euphorbiaceae) in Turkey and its taxonomic significance - Kursat, Murat; Baser, Birol; Ozbey, Fahrettin; Emre, Irfan (Tubitak Scientific & Technological Research Council Turkey, 2023)
The morphological characteristics of seeds are not affected by environmental factors and can be used to identify the Euphorbia taxa. The present study aims to determine the morphological characteristics of seeds in 27 taxa of Euphorbia using scanning electron microscopy (SEM) and light microscope (LM). Findings revealed that the seeds of Euphorbia show variation in size, color, and seed surface ornamentations among different species. The seeds vary also in shape from ovoid, ellipsoidal, globose, quadrangular, compressed, to compressed-ellipsoidal with two exceptions in E. petiolata (oblong-quadrangular truncate), E. macrocarpa (subglobose), and E. szovitsii var. kharputensis (ellipsoidal quadrangular truncate). Furthermore, it was demonstrated that caruncle color, shape, and surface are different in the studied Euphorbia spp. Special attention was also paid to lipid granules indicating their shape variation among taxa from globose, broad ellipsoidal globose to reniform, although the granules were absent in some taxa. In addition, some taxa lack any caruncle. The unweighted pair group method with arithmetic mean and principal component analysis was used to assess the morphological differentiation of the seeds among the studied taxa. According to the dendrogram and plot obtained from cluster and PCA analyses, Euphorbia taxa are divided into four clusters corroborating the previous molecular phylogenetic results.
Keywords: Caruncle; Euphorbia; LM; seed morphology; SEM